A 23-Year-Old Female with a Mixed Germ Cell Tumor of the Pituitary Infundibulum: The Challenge of Differentiating Neoplasm from Lymphocytic Infundibuloneurohypophysitis—A Case Report and Literature Review. (18th June 2014) - Mon, Sann Yu; Mahmud, Hussain; Abbasi, Munira; Murdoch, Geoff; Fernandez-Miranda, Juan C.; Gardner, Paul A.; Challinor, Sue M.
Abstract : The pathologic spectrum of diseases that infiltrate the pituitary infundibulum includes a broad variety of clinical entities. There are significant differences in the prevalence of these etiologies depending on the age of presentation. Lymphocytic infundibuloneurohypophysitis (LINH) predominates over other causes of infundibular disease in adults over age 21. Differentiating LINH from other causes of infundibular disease can be difficult because the various etiologies often have similar clinical presentations and radiologic imaging characteristics. We report the first case in an adult of a mixed germ cell tumor comprised of germinoma and embryonal cell carcinoma infiltrating the pituitary infundibulum. In our case, a 23-year-old female was initially misdiagnosed as having LINH. She presented with panhypopituitarism and diabetes insipidus, which is the most common initial presentation in both entities. The two diagnoses are difficult to distinguish based on MRI imaging, CSF findings, and histopathological examination. Our case demonstrates the need for close follow-up of patients with isolated lesions of the pituitary infundibulum and reinforces the need for biopsy of an infundibular lesion when progression of disease is demonstrated. In our case, biopsy with comprehensive immunohistochemical staining was the sole means of making a definitive diagnosis.